An empirical study of high performance HRM practices in Chinese SMEs - Zheng, C.; Morrison, M.; O'Neill, Grant (Routledge, 2006)
This paper explores the performance effects of human resource management (HRM) practices in 74 Chinese small and medium-sized enterprises (SMEs). Four high performance HRM practices are identified: performance-based pay, participatory decision-making, free market selection, and performance evaluation. Regression analysis results support the conventional idea that the adoption of HRM practices generates better HRM outcomes and, in turn, better HRM outcomes contribute positively to firm performance. However, not all HRM practices, and their effects, led to improved SME performance. Among the Chinese SMEs investigated, a high level of employee commitment was identified as being the key HRM outcome for enhancing performance.